Associations Between Parental Factors and Child Diabetes-Management–Related Behaviors. Issue 5 (June 2017) - Lohan, Aditi; Morawska, Alina; Mitchell, Amy
ABSTRACT: Objective: Adherence to diabetes-management regimens in children requires teamwork and consistency from both parents and children. This study investigated a mediational model developed to understand the relationship between different modifiable parent factors influencing child diabetes-related behaviors. Methods: We recruited 186 parents of children aged 2 to 10 years with Type 1 diabetes to complete self-report questionnaires on child diabetes behavior, parental self-efficacy with managing the child's behavior, parent diabetes self-efficacy, parent adjustment, condition management effort, parent perception of their diabetes knowledge, and parenting behavior. We used structural equation modeling in AMOS to test our hypothesized model of interrelationships between variables associated with child diabetes behavior. Results: The hypothesized model provided good fit to the data. We found that parent perception of low levels of diabetes knowledge and higher levels of condition management effort, and parent adjustment difficulties were associated with lower parental self-efficacy with diabetes management. This was further linked with lower levels of parental self-efficacy with managing their child's diabetes behavior, and consequently, higher extent of child diabetes behavior problems. Contrary to our expectations, we did not find a significant effect of parenting behavior on child diabetes behavior problems, either directly or indirectly via parent self-efficacy for managing child's behavior. Conclusion: Our findings shed light on the mechanisms through which different parenting factors interact and are associated with diabetes behavior in children. These factors can be targeted through parenting interventions to improve child's cooperation with diabetes-management tasks and reduce barriers to effective management. Abstract : This article has supplementary material on the web site: www.jdbp.org.